(untitled) (Journal of actual problems of jurisprudence, 2018)
This article considers theoretical issues of activity of government control bodies of in the sphere of labor relations, differentiation of their functions and ensuring legitimate rights and interests of workers. Key words: control bodies, state supervision and control.